(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This research investigated secoisolariciresinol diglucoside (SDG) flax extract effects on apoptosis, hedgehog (Hh), autophagy, and the anti-oxidation process in experimentally induced obesity. Materials and Methods: Forty rats were separated into two sets regarding either receiving a normal balanced diet or a high-fat diet (HFD) and then distributed into four groups: GI: The control group had a regular diet for 12 weeks. GII: animals received a high-fat meal and saline by gastric gavage. GIII: HFD obese rats treated with SDG extract orally (10 mg/kg/b.w.) and 1.18 mg SDG/kg in the diet for 4 weeks GIV: Normal balanced diet rats received SDG extract orally (10 mg/kg/b.w.) and 1.18 mg SDG/kg of chow for 12 weeks in addition to their regular balanced diet. Results: The administration of SDG extract exhibited a significant drop in body weight, glucose, lipid profile, and leptin compared to the obese group. It also improved the antioxidant levels (lowering the levels of malondialdehyde while increasing the total antioxidant capacity) and anti-inflammatory status (decreasing interleukin-6 and tumor necrosis factor-alpha). SDG extract downregulates the expression of HH genes (protein patched homolog 1, Hh-interacting protein, glioma-associated oncogene homolog 1, and smoothened receptor) in conjunction with the modulation of autophagy genes and apoptotic proteins. Conclusion: SDG extract showed improved anti-inflammatory and antioxidant status and downregulated the expression of HH genes while modulating autophagy genes and apoptotic proteins among obese rats, suggesting that it may be used to avert and manage obesity and its correlated complications by modulating oxidation, inflammation, autophagy, and apoptosis. Advanced future research on the SDG autophagy pathway to address obesity and its complications is mandatory. J. Adv. Vet. Anim. Res., 10(2): 321–335, June 2023 http://doi.org/10.5455/javar.2023.j684